Criteria evaluation for the transition of cracking modes in a single-crystal nickel-base superalloy. (April 2020) - Busse, C.; Gustafsson, D.; Palmert, F.; Sjödin, B.; Almroth, P.; Moverare, J.J.; Simonsson, K.; Leidermark, D.
Highlights: Evaluation of three different criteria to predict the cracking mode transition. Applicable to 3D models with arbitrary material orientation and crack front shapes. Calibrated by laboratory tests. A threshold value of a resolved shear stress intensity factor can be a criterion. Abstract: Single-crystal nickel-base superalloys frequently experience two distinct fatigue crack growth modes. It has been observed that, under certain conditions, cracks transition from a path perpendicular to the loading direction to a crystallographic slip plane. As crystallographic cracking is associated with an increased fatigue crack growth rate, it is important to be able to predict when this transition occurs. In this work three different criteria for crystallographic cracking based on resolved anisotropic stress intensity factors are evaluated in a three-dimensional finite element context. The criteria were calibrated and evaluated using isothermal fatigue experiments on two different specimen geometries. It is suggested by the results, that a threshold value of a resolved shear stress intensity factor can act as a conservative criterion indicating cracking mode transition. Further, a trend hinting towards a loading frequency dependency could be observed.